Predatory mites fauna on medicinal and aromatic plants from Sundarban Biosphere Reserve, West Bengal, India - Samaddar, Indrani; Podder, Sanjoy; Chakrabarti, Santanu; Biswas, Himani (Acta Biologica Szegediensis, 2022)
regular survey was conducted in different places of Sundarban Biosphere Reserve (SBR) region of West Bengal on 32 different medicinal and aromatic plants. A total of 41 species of predatory mites belonging to 19 genera, 7 families, under 2 orders were observed during this study. Collection data, distribution and keys are given for all taxonomic categories. Many of the species and habitats reported here are new records. Ecological and behavioral remarks on all the predatory mite species reported from Sundarban Biosphere Reserve are also presented.